Romaison 2020 Rome, an Extraordinary Maison: The Archives and Creations of Its Costume Studios, curated by Clara Tosi Pamphili. Issue 1 (1st June 2021) - Colombini, Grazia
Romaison 2020 Rome, an Extraordinary Maison: The Archives and Creations of Its Costume Studios, curated by Clara Tosi PamphiliMuseo dell'Ara Pacis, Roma, 23 October‐29 November 2020